A Study to Compare the Motorised Wedge Output Factor of an Elekta Synergy Linear Accelerator with Reference Data (TPS Data) - Akosah, K. (University of Ghana, 2016)
For external beam radiotherapy treatments, high doses are delivered to the cancerous cell. Accuracy and precision of dose delivery are primary requirements for effective and efficient cancer treatment. The dose delivered to the patient might not be uniform and therefore need to be compensated for. In treatment these inhomogeneities are taken care of by using wedge filters and incorporating wedge factors in the Treatment Planning System. Computer controlled wedges were alternatives introduced by different manufacturers of which Motorized wedges (MW) is one of them. The MW was introduced by ELEKTA and this helps to overcome some of the shortcomings of physical wedges. The objectives of this study were to measure MW output factors for 6 MV and 15 MV photon energies for an ELEKTA Synergy. Secondly, to compare the results of MWOF obtained to that of the treatment planning system data. The Motorized Wedge Output Factors (MWOF) were measured for the ELEKTA Synergy for both 6 MV and 15 MV photon energies. With the help of PMMA solid water slabs phantom, the Elekta synergy, thermometer, barometer, PTW farmer type ionization chamber 30010 charges were collected at 100 cm source to surface distance for various square field sizes from 5x5 cm to 30x30 cm and depth of 1.5 cm and 2.5 cm for 6 MV and 15 MV photon energies. Comparing the results with the TPS data, an excellent agreement was found for 6 MV MWOF, with the percentage differences ranging from 0.03% to 1.50%, with a mean of 0.03%. The coefficient of variation of MWOF ranged from 0.023% to 1.07% and 0.001% to 12.89% for the two beams (6 MV and 15 MV) respectively. The relative differences between the calculated and the measured MWOFs increases with field size. In conclusion, there was general agreement between the calculated and measured MWOFs. The consistency of values provide further support that a standard dataset of photon and electron dosimetry could be established as a guide for future commissioning, beam modeling, and quality assurance purposes.
Thesis (MPhil) - University of Ghana, 2016